Pelaksanaan Projek Penguatan Profil Pelajar Pancasila di SMA Negeri 3 Banda Aceh - Mardhiah, Ainul; Ariska, Dinda (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The implementation of P5 activities can create student characters based on the Pancasila student profile and can increase student creativity and independence. The problem faced by SMA Negeri 3 Banda Aceh is that it has implemented P5 activities but no research reports have been found or published. This study aims to analyze the stages of P5 implementation applied by the principal in the Analysis of the Implementation of the Pancasila Student Profile Strengthening Project at SMA Negeri 3 Banda Aceh. This study uses observation, interviews and documentation carried out by purposive sampling and snowball, so that interviews were conducted with six people, namely the vice principal of curriculum, vice principal of public relations, two teachers and two students. Data analysis uses data reduction, data presentation and drawing conclusions, so that data validity is checked, namely with credibility, transferability, dependability, and confirmability. The results of the study indicate that the stages of P5 implementation at SMA Negeri 3 Banda Aceh include intracurricular, co-curricular and extracurricular.